The Effect of Tourism Experience on Revisit Intention through Destination Image and Satisfaction - Atmari, Noveliana Violla; Putri, Vini Wiratno (Universitas Negeri Semarang, 2021)
The purpose of this study to examine the influence of tourism experience on revisit intention mediated by destination image and satisfaction. Sampling technique using the accidental sampling and purposive sampling with sample of 240 respondents. Respondents were taken from visitors who had been to Sanggaluri Park Purbalingga twice or more and aged 17 years or over. Method of data collection using the questionnaire. The data analysis method uses the Structural Equation Model - Partial Least Square (SEM-PLS) with the Smartpls program. The direct test result show the result of tourism experience has a direct effect on destination image, tourism experience has a direct effect on satisfaction, tourism experience has a direct effect on revisit intention.